Fungal Contaminants in Tissue Culture of Date Palm (Phoenix dactylifera L.): Problems and Solutions. (review article) - Ahmed, Alaa N. (Basrah Journal Of Date Palm Research, 2023)
Date palm is one of the most important economic species for the palm family. It is primarily cultivated for its fruits. Various propagation methods have been used to meet the increasing demand for date palm trees worldwide. Tissue culture propagation has been widely used in many countries, including Iraq. Tissue culture propagation faces several obstacles, including contamination with microorganisms, which poses a significant challenge for successful and sustainable propagation of date palm in tissue culture laboratories. Two main groups of contaminants have been identified and isolated from different date palm tissue culture laboratories in Iraq, namely fungi and bacteria. These groups are major contributors to contamination in date palm tissue culture farms, leading to significant losses in plant tissue culture farms. This article provides a general overview of fungi isolated from date palm farms in Iraq and their impact on the success of tissue culture propagation, shedding light on the methods used to reduce fungal contamination in date palm tissue culture farms.